INCIDENCIA DEL CLIMA LABORAL EN LA ROTACIÓN DEL PERSONAL EN LOS EMPLEADOS DEL MINISTERIO DE DESARROLLO URBANO Y VIVIENDA - LOJA. - Quizhpe Pinta, Andreina Stefania (2021)
The present work of investigation is directed to know the incidence of the labor climate in the rotation of the personnel of the employees of the Ministry of Urban Development and Housing - Loja; this being its general objective. The research focused on carrying out the analysis of the different factors of the work environment that occur in the institution, to analyze each factor the design of the non-experimental research was prepared, it was based on the collection of information for the diagnosis of the real situation of the institution, managing to establish that the factors that directly affect staff turnover are: remuneration and motivation. With the application of statistical tools such as the previously designed survey and interview, it was possible to know the problems faced by employees. In the results obtained, it is observed that all the factors under analysis have deficient values, which causes the staff to be unmotivated. In the analysis of the other factors, the results obtained show a fairly acceptable average, confirming that the work environment does have an impact on staff turnover, once the analysis and discussion of the results have been developed, the conclusions and recommendations are presented. Finally, a proposal is presented, proposing alternative solutions to each of the research factors that require priority attention from the institution in order to achieve optimal development and fulfillment of its objectives.